2021
DOI: 10.3390/molecules26175157
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Microencapsulation of Soybean Oil and Vitamin D Using Bare Glycogen Nanoparticles

Abstract: Ultrasonically synthesized core-shell microcapsules can be made of synthetic polymers or natural biopolymers, such as proteins and polysaccharides, and have found applications in food, drug delivery and cosmetics. This study reports on the ultrasonic synthesis of microcapsules using unmodified (natural) and biodegradable glycogen nanoparticles derived from various sources, such as rabbit and bovine liver, oyster and sweet corn, for the encapsulation of soybean oil and vitamin D. Depending on their source, glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Liu et al, (2022) reported the increased particle size by the addition of Arabic gum and polydispersity index of the ternary complex was dramatically reduced after ultrasound treatment; the absolute values of zeta potential were increased. Previously published findings (Liu et al, 2022;Ahmad and Gani, 2020;Cimino et al, 2021) were consistent with the results of the present study. Due to the results, the use of the CS: Hicap wall materials ratio (1.5%:8.5%) showed a smaller size compared with other formulations prepared with different concentration of wall materials.…”
Section: Resultssupporting
confidence: 94%
“…Liu et al, (2022) reported the increased particle size by the addition of Arabic gum and polydispersity index of the ternary complex was dramatically reduced after ultrasound treatment; the absolute values of zeta potential were increased. Previously published findings (Liu et al, 2022;Ahmad and Gani, 2020;Cimino et al, 2021) were consistent with the results of the present study. Due to the results, the use of the CS: Hicap wall materials ratio (1.5%:8.5%) showed a smaller size compared with other formulations prepared with different concentration of wall materials.…”
Section: Resultssupporting
confidence: 94%
“…The encapsulation efficiency, storage stability, and minimization of oil release throughout digestion are very important for oils [71][72][73][74][75][76][77]. The encapsulation efficiency of SB oil using different matrices and capsule types was moderate.…”
Section: Discussionmentioning
confidence: 99%
“…They also constructed soft GNPs with a diameter of 20 nm which can deliver siRNAs in human prostate cancer cells more effectively and lead to a 60% gene silencing effect [ 203 ]. The size of glycogen is important for the stability of NPs loaded with siRNA as well, as GNPs with a smaller size and a higher protein content are more likely to maintain stability [ 204 ].…”
Section: Np Delivery—a Platform Ensuring the Efficacy And Stability O...mentioning
confidence: 99%